Human rights : an interdisciplinary approach - Freeman, Michael, 1936- (Cambridge, UK : Polity Press, 2011)
Introducing readers to the theory and practice of human rights, this text emphasises how the experiences of the victims of human rights violations are related to legal, philosophical and social-scientific approaches to human rights.
Introduction: thinking about human rights -- Origins : the rise and fall of natural rights -- After 1945 : the new age of rights -- Theories of human rights -- The role of the social sciences -- Universality, diversity and difference : culture and human rights -- The politics of human rights -- Globalization, development and poverty : economics and human rights -- Human rights in the twenty-first century.
Includes bibliographical references (p. [212]-234) and index.
Keywords: Human rights; Politics and Government; Mensenrechten